The patterns of war since the eighteenth century - Addington, Larry H. (Indiana University Press, 1994)
Presents a history of the evolution of warfare from the American Revolution to Operation Desert Storm. This work discusses developments in strategies and tactics, logistics and weaponry, and provides discussions of important battles and campaigns. It serves as an introduction for both students and the general reader.